The Transmission Structure and Communal Identity of the Sanshinje in Yeonchuk-dong: An Oral History Approach - Noh, Younghee (International Journal of Knowledge Content Development & Technology, 2025)
Purpose: This study examines the Sanshinje (mountain spirit ritual) of Yeonchuk-dong, Daejeon, as a living form of folk belief embedded in communal practice. Methodology: Based on 2025 oral history documentation, the research adopts folkloristic ethnography, symbolic interpretation, and community theory to analyze the ritual’s structure and meaning. Result: Findings show that the Sanshinje functions as a symbolic and ethical system sustaining collective identity and memory. The sacrificial use of a bull reflects regional uniqueness and communal solidarity. Institutional support through a preservation committee has enabled the ritual’s continuity despite social change. Implication: The study emphasizes the need to preserve Sanshinje as community-owned living heritage, maintaining authenticity while adapting to modern challenges.